PROVINCIAL CAPITAL EXPENDITURE AND THE FACTORS INFLUENCE THE BUDGET: BEFORE AND AFTER THE GOVERNOR ELECTION - Yaya, Rizal; Savitri, Diah (Muhammadiyah International Journal of Economics and Business, 2019)
This study aims to find out factors that have influence on capital expenditure in provincial government before and after the Governor election. It involved 32 provincial governments in Indonesia as the sample. The sampling technique was purposive sampling. The secondary data was obtained from the report of budget realization of provincial government in Indonesia. The methodology of analysis was multiple linear regression analysis. The result of this study shows that both local revenue and area size have positive effect on capital expenditure. Meanwhile, Special Allocation Fund has negative effect on capital expenditure. In overall, the independent variable explains 65.9% of the dependent variable, while the rests are influenced by other variables not analyzed in this study.